Antecedents of Willingness to Communicate in Online ESP Conversation Classes: A Cognitive, Affective, and Situational Perspective - Susilawati Susilawati; Suwantica Kusumandari; Arrizqi Ramadhan (Universitas Muhammadiyah Mataram, 2026)
Abstract: Communication studies students are required to develop effective oral communication skills in English for Specific Purposes (ESP) courses to support academic and professional readiness, including in online learning environments. Although previous studies have explored willingness to communicate (WTC) in ESP and English as a Foreign Language (EFL) contexts, limited attention has been paid to communication studies students and online ESP conversation classes. This qualitative case study explores the cognitive-linguistic, affective, and situational antecedents shaping WTC among 45 communication studies students at a university in Central Jakarta. Data were collected through open-ended questionnaires. In cognitive-linguistic readiness, the students demonstrate awareness of the importance of English communication and employ cognitive strategies such as planning and lexical preparation, although some speaking elements are still developing. Affective factors, including speaking enjoyment and topic interest, as well as situational factors comprising supportive lecturer feedback and instructional clarity, stimulate the students' WTC. The study further suggests that the online learning environment functions as a space that shapes speaking readiness. The study recommends incorporating more authentic professional communication activities in ESP online classrooms to strengthen students’ employability skills.Abstrak: Mahasiswa jurusan studi komunikasi dituntut untuk mengembangkan keterampilan komunikasi lisan yang efektif dalam mata kuliah Bahasa Inggris untuk Tujuan Khusus (ESP) guna mendukung kesiapan akademis dan profesional, termasuk dalam lingkungan pembelajaran daring. Meskipun studi sebelumnya telah mengeksplorasi kesediaan untuk berkomunikasi (WTC) dalam konteks ESP dan EFL, perhatian yang diberikan kepada mahasiswa jurusan studi komunikasi dan kelas percakapan ESP daring masih terbatas. Studi kasus kualitatif ini mengeksplorasi anteseden kognitif-linguistik, afektif, dan situasional yang membentuk WTC di antara 45 mahasiswa jurusan studi komunikasi di sebuah universitas di Jakarta Pusat. Data dikumpulkan melalui kuesioner terbuka. Dalam kesiapan kognitif-linguistik, mahasiswa menunjukkan kesadaran akan pentingnya komunikasi bahasa Inggris dan menerapkan strategi kognitif seperti perencanaan dan persiapan leksikal, meskipun beberapa elemen berbicara masih dalam tahap perkembangan. Faktor afektif, termasuk kesenangan berbicara dan minat terhadap topik, serta faktor situasional yang meliputi umpan balik dosen yang mendukung dan kejelasan instruksional, menstimulasi WTC mahasiswa. Studi ini lebih lanjut menunjukkan bahwa lingkungan pembelajaran daring berfungsi sebagai ruang untuk membentuk kesiapan berbicara. Studi ini merekomendasikan memasukkan lebih banyak aktivitas komunikasi profesional yang otentik di kelas daring ESP guna memperkuat keterampilan kerja mahasiswa.